Digital Agriculture, Methods and Applications - Shamshiri, Redmond R.; Shafian, Sanaz (IntechOpen, 2022)
Digital technology has helped researchers and growers to embrace the uncertainties involved in different aspects of crop production via a sense-process-act paradigm that is referred to as Digital Agriculture. The ultimate objective of this concept is to optimize the food production process and increase efficiencies. To achieve this, a combination of methods, tools, and software is used to collect data, extract the correct information, and implement the right actions. Although some of the technology and methods involved in these practices, such as Geographic Information System (GIS), yield monitoring platforms, and variable-rate applications have been previously studied under the label of Precision Agriculture, their impact on the entire Agri-Food value chain, as well as the relatively newer concepts such as the Internet-of-Things, agricultural robotics, artificial intelligence, mobile apps, digital twins, and blockchain fall under the scope of Digital Agriculture. This book provides the reader with an overview of the technologies involved in the digitalization of agriculture, as well as the data processing methods, decision-making process, and innovative wireless solutions for implementing responses and actions. Each chapter is focused on a specific aspect of the digitalization of agriculture to engage with the academic community and end-user farmers.